SERS as an analytical tool in environmental science: The detection of sulfamethoxazole in the nanomolar range by applying a microfluidic cartridge setup - Patze, Sophie; Huebner, Uwe; Liebold, Falk; Weber, Karina; Cialla-May, Dana; Popp, Juergen (Analytica chimica acta, 2017)
Sulfamethoxazole (SMX) is a commonly applied antibiotic for treating urinary tract infections; however, allergic reactions and skin eczema are known side effects that are observed for all sulfonamides. Today, this molecule is present in drinking and surface water sources. The allowed concentration in tap water is 2·10−7 mol L−1. SMX could unintentionally be ingested by healthy people when drinking contaminated tap water, representing unnecessary drug intake. To assess the quality of tap water, fast, specific and sensitive detection methods are required, in which consequence measures for improving the purification of water might be initiated in the short term. Herein, the quantitative detection of SMX down to environmentally and physiologically relevant concentrations in the nanomolar range by employing surface-enhanced Raman spectroscopy (SERS) and a microfluidic cartridge system is presented. By applying surface-water samples as matrices, the detection of SMX down to 2.2·10−9 mol L−1 is achieved, which illustrates the great potential of our proposed method in environmental science.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Environmental safety; Microfluidics; Molecular orientation; Sulfamethoxazole detection; Surface enhanced Raman spectroscopy